Analysis of the Availability of Laboratory Tests to the Number of Requests for Tests and Its Implications on Patient Satisfaction - Ivana Yolanda; Vip Paramarta (CV. Publikasi Indonesia, 2024)
This study aims to analyze the availability of laboratory tests based on the number of test requests and their implications for patient satisfaction. Health laboratories are a vital component of healthcare services, providing accurate laboratory test results to support patient diagnosis and treatment. The availability of fast and accurate laboratory tests plays a crucial role in speeding up diagnosis and treatment, which ultimately impacts patient satisfaction. However, many healthcare facilities face challenges in providing adequate laboratory test availability, such as limitations in equipment, expertise, and inefficient procedures. This study employs a literature review approach to collect, analyze, and synthesize information from various relevant sources. The findings reveal that the availability of fast and accurate laboratory services can enhance patient satisfaction, while limitations in availability can lead to dissatisfaction and increased waiting times. Therefore, effective laboratory management is essential to improve service quality and patient experience in hospitals. This research is expected to provide valuable insights for improving the healthcare system, particularly in laboratory management.